Microtropis cerocarpa (Celastraceae), a new species from southern Vietnam - Savinov, Ivan A.; Nuraliev, Maxim S.; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Luu, Hong Truong; Tran, Huu Dang; Luong, Huu Thanh (Phytotaxa, 2019)
Microtropis cerocarpa, a new species of Celastraceae, is described and illustrated. The species was discovered in 2012 during a botanical survey of the Chu Yang Sin National Park (Dak Lak province, southern Vietnam); additional collections were obtained there in 2018. Microtropis cerocarpa possesses dense glomerate sessile inflorescence with sessile flowers which allows placing this species into sect. Microtropis. Within this section it is most similar to M. obscurinervia, M. rhynchocarpa and M. wui. The new species differs from related species mainly by large thick leaves 23.5–39 cm long and 13–22 cm wide with very short petiole (subsessile) and cordate base, fruit with short rostrum of 1–2 mm long at apex, and immature fruit surface with a pronounced white wax coating in the form of granules. Microtropis cerocarpa is an easily recognized tree with remarkable robust habit and large leaves. A description of the vegetation in the area inhabited by M. cerocarpa is provided. The data on species diversity of Microtropis in Vietnam are summarized and an identification key is compiled.